Control wildfire-induced Microcystis aeruginosa blooms by copper sulfate: Trade-offs between reducing algal organic matter and promoting disinfection byproduct formation - UZUN, HABİBULLAH (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Elevated levels of nutrients due to wildfire ash input into stream waters will likely cause algal blooms. When source water is impeded by algae and requires immediate restoration, copper algaecides are usually applied. Previous studies indicate that Cu2+ can promote reactivity of dissolved organic matter in forming disinfection byproducts (DBPs). However, it is unclear that how DBP formation is changed after the treatment of post-fire algal bloom by copper algaecide. In this study Microcystis aeruginosa was cultured in the medium containing black and white ash water extracts (BE and WE) to study DBP concentrations before and after 4-days exposures to low and high copper sulfate (0.5 and 1.0 mg-Cu/L). Dissolved organic matter (DOM) was characterized by UV-VIS absorption and fluorescence spectroscopy and chlorination/chloramination-based DBP formation potential (FP) experiments. DOM concentrations and algal population in the treatments were lower than that in control, regardless of types of water extract. N-nitrosodimethylamine FP in the treatments were 4-6 times higher than the control (0.23-0.34 vs. 0.05-0.06 mu g/L), while haloacetonitrile FP revealed no significant difference (132-191 vs. 167-185 mu g/L). Trade-offs between reducing algal population and promoting DBP-FP were more pronounced for the solutions containing BE than WE. Low copper concentration was as effective as high concentration in inhibiting algal growth while minimizing promotion of DBP formation. The results can serve to support risk evaluations of algal population and DBP concentration when wildfire-induced algal bloom is left untreated and treated by copper algaecides. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Wildfire ash; Algal bloom; Microcystis aeruginosa; Copper algaecide; Disinfection byproducts; DRINKING-WATER; METAL-IONS; CHEMICAL-COMPOSITION; CORROSION PRODUCTS; DBP FORMATION; GREEN-ALGAE; CHLORINATION; COMPLEXATION; BINDING; ACID